Vascular pharmacology : cytoskeleton and extracellular matrix - Khalil, Raouf A. (Advances in pharmacology (San Diego, Calif.) ;, 2018)
Latest information on the vascular cytoskeleton and extracellular matrix presented with helpful illustrations and supporting references by prominent scientists and highly-recognized experts in the vascular field. Topics of interest in this new release include Pharmacology of the Vascular Cytoskeleton and Extracellular Matrix, The Dynamic Actin Cytoskeleton in Smooth Muscle, The Role of the Actin Cytoskeleton in the Regulation of Vascular Inflammation, The Smoothelin Family of Proteins and the Smooth Muscle Cell Contractile Apparatus, Smooth Muscle Cytoskeletal Network Regulates Expression of the Profibrotic Genes PAI-1 and CTGF, and more.